2023
DOI: 10.1002/eqe.3900
|View full text |Cite
|
Sign up to set email alerts
|

Seismic damage and functional loss of ceiling systems: Observation in shaking table test of hospital specimen

Abstract: This paper presents seismic damage to continuous ceiling systems and the impact of damage on functionality in the hospital specimen tested at the E-Defense shaking table. The specimen had four ceiling systems with different peripheral constraint conditions, coverage areas, suspended lengths, and ceiling panel materials. The test results demonstrate that the continuous ceiling system is less susceptible to collapse than the lay-in ceiling system. However, medical facilities require maintaining functionality aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There are a wide variety of building services, including electrical; heating, ventilation, and air conditioning (HVAC); sanitary; vertical transport; and life safety (i.e., fire safety in indoor environments [18]) systems. Numerous studies [19][20][21][22][23], including full-scale experiments, numerical analyses, and earthquake damage surveys, have demonstrated that building services components are typically vulnerable to building shaking, yet they can be protected via improved building design [24]. A post-earthquake functionality evaluation of the building services is therefore an important element in measuring the seismic resilience of buildings [25] to support engineering decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…There are a wide variety of building services, including electrical; heating, ventilation, and air conditioning (HVAC); sanitary; vertical transport; and life safety (i.e., fire safety in indoor environments [18]) systems. Numerous studies [19][20][21][22][23], including full-scale experiments, numerical analyses, and earthquake damage surveys, have demonstrated that building services components are typically vulnerable to building shaking, yet they can be protected via improved building design [24]. A post-earthquake functionality evaluation of the building services is therefore an important element in measuring the seismic resilience of buildings [25] to support engineering decision-making.…”
Section: Introductionmentioning
confidence: 99%